If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = w + 6 Reorder the terms: 23 = 6 + w Solving 23 = 6 + w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 23 + -1w = 6 + w + -1w Combine like terms: w + -1w = 0 23 + -1w = 6 + 0 23 + -1w = 6 Add '-23' to each side of the equation. 23 + -23 + -1w = 6 + -23 Combine like terms: 23 + -23 = 0 0 + -1w = 6 + -23 -1w = 6 + -23 Combine like terms: 6 + -23 = -17 -1w = -17 Divide each side by '-1'. w = 17 Simplifying w = 17
| 1-2tan^2x=-tan^2x | | 0.25(y-4)+.03y=0.18y-0.05(40) | | j+j-j=11 | | -16t^2+84t+112=0 | | 6.3/0.9-(-4.1)x(-0.4) | | 8y-2(5+2y)=7y-16 | | 2 = 12(9x+8) | | -3(3x-3)-9=-2(7x+3)-3 | | 16t^2+84t+112=0 | | 3x+6=27+y | | 7y+-42x+7=0 | | -8-6=7x-2-6x | | 6x-(8X+9)=2x-17 | | 9x+16y=-2 | | Sqrtx^2+7=x+1 | | 5*(x+8)=110 | | 26-u=234 | | 41.73/4.00x | | -4(3y+2x)= | | 70=164-v | | 6.78=2X/0.4-X | | 11x-67=77+2x | | x+x+1+x+2+x+3=-74 | | 3=23-5m | | -3(9+-2y+2.5z)+5y+2z=-27 | | 6(ax+3b)= | | 3+3x-1=9x+4-7x | | 14=4g-2 | | -4+(-24)=12 | | x-(3+x)+6=x-2[x-(3x+4)] | | (x-2)^1/2=(28-2x)^1/4 | | 8(3k-7)=64 |